Integrating top-down and bottom-up approaches for climate adaptation planning in agriculture : the case of the Lower Bhavani Irrigation Project, India - Kamalamma, Ambili Gopalan; Babel, Mukand S.; Shanmugam, Mohana Sundaram; Shrestha, Sangam; Datta, Avishek; WEM Projects; AIT Fellowship (Pathum Thani, Thailand : Asian Insititute of Technology, 2024)
Adapting to a climate-sensitive future necessitates accounting for non-stationary climate conditions under deep uncertainty conditions. Two main approaches are followed for planning adaptation options in agriculture: top-down and bottom-up approach. Application of top-down approach in adaptation planning will not suggest whether the options selected would work for a full range of potential future climate states as the local system characteristics are also not considered. Hence this study proposes using an integrated top-down and bottom-up approach to plan for adaptation, by assessing the risks of the irrigated agriculture system of Lower Bhavani Irrigation Project (LBIP) of India to climate related stressors or drivers. This study used a novel Climate Risk Informed Decision Analysis (CRIDA) approach for adaptation planning in the agricultural sector. CRIDA is a bottom-up approach intended to address the deep uncertainty associated with climate adaptation planning. Climate conditions causing risks to the irrigated agriculture system were identified through climate change projections done with 10 Regional Climate Models (RCMs) selected from a list of 27 RCMs under the South Asia domain of CORDEX, under two Representative Concentration Pathways (RCPs) and in two future time periods of near future (2021-2050) and mid future (2051-2080). The decision context was established, where decision variables were fixed, the performance metrics and their thresholds were identified. To account for changes in both precipitation and temperature, two decision variables or stressors were used {u2013} Aridity index (AI), which is the ratio of precipitation to the potential evapotranspiration and the climate variability, expressed as coefficient of variation of precipitation. Yield ratio (ratio of actual/model simulated yield to the normal or long-term yield, taken as 4t/ha for paddy) and supply-demand ratio, both with threshold value of 1, were identified as the performance metrics. To understand the vulnerability of the system, stress testing was done by incrementing the climate variables. Stress response surfaces were created indicating the system response to climate variability and change. A risk matrix was also developed by considering both the impacts and plausibility of future climate conditions. Two different adaptation strategies were identified- water management and crop management, with three adaptation measures under the first strategy- aerobic rice cultivation, alternate wetting and drying, deficit irrigation, and changing the cropping calendar under the second strategy {u2013} by early transplanting and delayed transplanting by one week and two weeks. These measures were tested for their financial feasibility as well as robustness and adaptation pathways were developed. Projections showed that the average annual precipitation, maximum and minimum temperatures will increase both in the near future and in mid future, under both RCP4.5 and RCP8.5. However, monthly rainfall projections by all models are not in agreement, pointing to the uncertainty in projections. Vulnerability assessment indicates that at lower AI, the yield is more sensitive to climate change whereas at high AI, both yield and supply-demand ratio is sensitive to both climate change and variability. For yield ratio, a decrease in aridity index increases the yield, whereas the response is vice versa in the case of supply-demand ratio. Overlaying the projections on the generated stress response surface had shown that they are below the threshold value of 1, showing that the generated future conditions are in fact plausible. Paddy yield in the irrigation project is at low risk to climate change and variability, but the system is at high risk due to the mismatch of supply and demand. Hence, adaptation strategies are recommended that include demand management options, whereas the adaptation needed in the case of yield reduction can be delayed. The plans must also be robust to account for the uncertainty in the projections of the various climate models used. Of the adaptation measures tested, only three which are under the water management scenario are preferred based on their robustness and risk reduction potential. The financial feasibility analysis had shown that additional investments made to make the system more robust is justifiable. Adaptation pathways developed show that deficit irrigation will work without failure for the entire planning period under the low emission scenario, when it is implemented individually or as a sequence with aerobic rice and AWD. However, implementing aerobic rice or AWD offers the flexibility to change the course of adaptation path in the future, depending on the availability of resources. Due to its system-relevant solutions, the integrated approach is advocated for local agriculture adaptation planning.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Water Engineering and Management
Thesis (Ph.D.) - Asian Insitute of Technology, 2024
Keywords: Climatic changes -- India -- Case studies; Water resources development -- India -- Planning; Agriculture -- India -- Planning